Analysis of Food Reserves In Makassar City - Arifianto, Andi Eka (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
The availability of food, particularly rice, is a key prerequisite for achieving food security in Makassar City. The average rice production in Makassar is only 7,281.98 tons per year, far below the community’s consumption needs, which reach 165,424.77 tons annually. This gap has driven efforts to meet food needs through various sources, including local production and Regional Government Food Reserves. From 2017 to 2023, the Government Food Reserves of Makassar City amounted to only 74 tons, which remains insufficient to anticipate food crises or emergency situations. Based on this condition, this study aims to analyze the causes of the limited amount of government food reserves in Makassar City. The method used is quantitative analysis. The study results indicate that one of the main causes of the low food reserves is outdated regulation. Makassar Mayor Regulation Number 38 of 2017 concerning the Management of Government Food Reserves is considered misaligned with higher-level policies. Therefore, it is recommended that the regulation be revised and elevated to the status of a Regional Regulation. With the establishment of a Regional Regulation, the implementation of food reserves by the Makassar City Food Security Office can be optimized to increase both the quantity and preparedness of food reserves. The proposed Regional Regulation can be initiated by the Food Security Office through several stages, including planning, drafting, deliberation, enactment, and finally promulgation in the Regional Gazette.